"We Females Have to Be Contented with the Tales of Adventures": Trauma and Gender in Dorothy Day's Early Reporting. Issue 1 (2nd January 2021) - Dick, Bailey
Abstract : This examination into the early writings of radical Catholic activist and newspaper founder Dorothy Day will explore how she fits into a cohort of journalists whose experiences with trauma both drove and shaped their written work. However, unlike many other traumatized journalists or women writers at the time, Day's reflections on her trauma allowed her to embrace her own experiences of suffering and emotion in her writing that evolved into the deeply personal, yet empowering writing style for which the Catholic Worker is renowned. This finding is revealed through a close reading of Day's personal papers at Marquette University, as well as her work published in the Call, the New Masses, and the New Orleans Item . These primary documents serve as a supplement to published letters, oral histories, and news articles written about Day's life.